Justice enablers of climate-health adaptation in South America - Romina Rekers; María Victoria Gerbaldo; Carlos Yabar; Cintia Rodríguez Garat; Lucas Rekers (The Journal of Climate Change and Health, 2025)
Background: Integrating justice enablers into climate-health adaptation planning reduces failed adaptation, prevents maladaptation, and facilitates transformative change in health systems. This is particularly necessary in South America (SA), where climate adaptation research and policy are financially constrained. By carefully considering differentiated climate-health risks and necessary trade-offs, National Adaptation Plans (NAPs) and Health National Adaptation Plans (HNAPs) provide forums for identifying just adaptation paths. This study assesses the integration of recognitional, procedural, and distributive justice enablers in climate-health planning in SA. Methods: Justice enablers were tracked within the actionable sections of the NAPs, HNAPs, or their Subsidiary Adaptation Strategies (SASs) of the South American countries. The level of integration of justice enablers was measured using keywords from the climate adaptation literature. Results: There is a significant disparity among countries in the level of integration of justice enablers in national adaptation planning. There is also significant variation across countries in the integration of different dimensions of justice (recognitional, procedural, distributive). Most countries score higher on the integration of recognition justice than on procedural and distributive justice. Conclusion: Comprehensive frameworks are required to integrate justice considerations into climate-health adaptation planning in a way that avoids failed adaptation or maladaptation.